Composite Animals: Then and Now. (9th December 2022) - Hinterberger, Amy
Abstract: Since the early twentieth century, the term "chimera" has been used to describe many experimental composite plants and animals. Composite animals and embryos, involving the transfer of cells from different species to make chimeras, continue to be a fundamental cornerstone of biomedical research. However, the twenty‐first century appears to be offering a new role for composite animals. Over the last fifteen to twenty years, composite animals and embryos have taken on a different form of life—an institutional life. With this institutional life, I argue, comes an opportunity to recast differences between humans and other animals and to reconsider how research on human health is governed .